GENEROS CUPHOCERINOS DE TAQUINIDOS CHILENOS (Acta Entomológica Chilena, 2022)
Chilean Cuphocerini Tachinid flies (Tachininae) comprises in Ihis revisión 13 genera and 31species nationally distributed in this country from Arica (Lat. So. 18fi) down to Magallanes (Lat. So56s) and from the Pacific to the high Andes. Allelomyia is herein described as a new monotypicgenus cióse to Trichophoropsis Townsend, while Dolichostoma nigricaudum (Blanchard), fromTucumán, Argentina, is for the first time recorded from Northern Chile. Spanipalpus picturatiis andS. rubidus are described as new species, as well as Vibrissomyia concinnata, Trichophoropsisbicolor and T. coscaroni. A key to all included genera is also offered plus pardal keys to ChileanSpanipalpus Town. and Vibrissomyia Town. Group characters of the Tribe are discussed poindngout some extra limital frequent anomalies in Spanipalpus, Vibrissomyia et. al., which after furtherrevisión of larger series of examples may eventually reveal unexpected new sinonimies. All thematerial referred to in this paper belongs to the Insects Collection of the Instituto de Entomología(IEUMCE) where it remain deposited together wilh types.